Leadership Styles in Architectural Design Offices in Turkey - Kasapoğlu, Esin (Asce-Amer Soc Civil Engineers, 1801 Alexander Bell Dr, Reston, Va 20191-4400 Usa, 2014)
The quality of a project depends on the performance of the design team; design faults can be prevented by effective team management. In this context, effective leadership is needed to enable effective team management. The preference for more than one style of leadership is inevitable in complex business life because different styles are contingent on different situated contexts. This paper focuses on determining which of the two leadership styles architects predominantly prefer in Turkey, and whether there are any differences in the preferences of leadership styles between the design and production phases in a construction context. Data were collected through a questionnaire on leadership styles, which was distributed to 40 architects from different design offices in Turkey. The leadership styles are gathered into two primary groups: transactional and transformational leadership styles. Two styles fall under transactional leadership-coercive and authoritative-and four styles fall under transformational leadership-affiliative, democratic, coaching, and pacesetting. The results show that Turkish architects prefer affiliative, authoritative, and pacesetting leadership styles, but when two styles need to be combined, their choices are the affiliative-democratic and affiliative-coaching leadership styles. Within the frame of this research, the leadership preferences of leading Turkish architects are discussed in light of Hofstede's parameters on Turkish national culture. Within this context, compatibility with the national culture of the leaders' preferences for these behaviors may affect the overall performance of architectural design teams. (C) 2013 American Society of Civil Engineers.
Keywords: Leadership styles; Construction project management; Architect; Architectural design team; Turkey; Organizational issues; Organizational Culture; Construction; Professionals; Firms